Artificial Intelligence: A New Era of Human Resource Management for Enhancing Employee Efficiency in The Healthcare Sector - Alina-Georgiana PETRE (Revista de Management Comparat International, 2025)
Artificial intelligence plays a crucial role nowadays at a global level, making its presence felt in almost all sectors of human activity due to its complex potential of applicability. The benefits of artificial intelligence can also be observed in the healthcare sector, where the main resource used to provide healthcare services is human resources. The purpose of this study is to highlight the potential impact that artificial intelligence can have in increasing the efficiency of managing human resources within healthcare institutions, by implementing artificial intelligence at the level of various human resource management structures.The results of this study indicated significant correlations between the efficiency of human resource management and employee behavior monitoring, employee stress monitoring, employee evaluation system, and skill development. These findings highlight that the implementation of AI in various work structures of human resource management can increase employee efficiency and, implicitly, employee workplace satisfaction.